New constraints for supernova models from presolar silicon carbide X grains with very high 26Al/27Al ratios - Hoppe, Peter; Leitner, Jan; Pignatari, Marco; Amari, Sachiko (The astrophysical journal. Part 2, Letters, 2023)
We report C, N, Mg-Al, Si, and S isotope data of six 1-3 μm-sized SiC grains of Type X from the Murchison CM2 chondrite, believed to have formed in the ejecta of core-collapse supernova (CCSN) explosions. Their C, N, and Si isotopic compositions are fully compatible with previously studied X grains. Magnesium is essentially monoisotopic 26Mg which gives clear evidence for the decay of radioactive 26Al. Inferred initial 26Al/27Al ratios are between 0.6 and 0.78 which is at the upper end of previously observed ratios of X grains. Contamination with terrestrial or solar system Al apparently is low or absent, which makes the X grains from this study particularly interesting and useful for a quantitative comparison of Al isotope data with predictions from supernova models. The consistently high 26Al/27Al ratios observed here may suggest that the lower 26Al/27Al ratios of many X grains from the literature are the result of significant Al contamination and in part also of an improper quantification of 26Al. The real dispersion of 26Al/27Al ratios in X grains needs to be explored by future studies. The high observed 26Al/27Al ratios in this work provide a crucial constraint for the production of 26Al in CCSN models. We explored different CCSN models, including both “classical” and H ingestion CCSN models. It is found that the classical models cannot account for the high 26Al/27Al ratios observed here; in contrast, H ingestion models are able to reproduce the 26Al/27Al ratios along with C, N, and Si isotopic ratios reasonably well.